Quantification of a professional football team's external load using a microcycle structure - Martin-Garcia, A.; Gomez Diaz, A.; Bradley, P. S.; Morera, F.; Casamichana, D. (The Journal of Strength and Conditioning Research, 2018)
The aims of this study were to (a) determine the external load of a football team across playing position and relative to competition for a structured microcycle and (b) examine the loading and variation the day after competition for players with or without game time. Training and match data were obtained from 24 professional football players who belonging to the reserve squad of a Spanish La Liga club during the 2015/16 season using global positioning technology (n = 37 matches and n = 42 training weeks). Training load data were analyzed with respect to the number of days before or after a match (match day [MD] minus or plus). Training load metrics declined as competition approached (MD-4 > MD-3 > MD-2 > MD-1; p < 0.05; effect sizes [ES]: 0.4-3.1). On the day after competition, players without game time demonstrated greater load in a compensatory session (MD + 1C) that replicated competition compared with a recovery session (MD + 1R) completed by players with game time (MD + 1C > MD + 1R; p < 0.05; ES: 1.4-1.6). Acceleration and deceleration metrics during training exceeded 50% of that performed in competition for MD + 1C (80-86%), MD-4 (71-72%), MD-3 (62-69%), and MD-2 (56-61%). Full backs performed more high-speed running and sprint distance than other positions at MD-3 and MD-4 (p < 0.05; ES: 0.8-1.7). The coefficient of variation for weekly training sessions ranged from ~40% for MD-3 and MD-4 to ~80% for MD + 1R. The data demonstrate that the external load of a structured microcycle varied substantially based on the players training day and position. This information could be useful for applied sports scientists when trying to systematically manage load, particularly compensatory conditioning for players without game time.